Sex and age bias viral burden and interferon responses during SARS-CoV-2 infection in ferrets - Magen E. Francis (Nature Portfolio, 2021)
Abstract SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) hospitalizations and deaths disportionally affect males and older ages. Here we investigated the impact of male sex and age comparing sex-matched or age-matched ferrets infected with SARS-CoV-2. Differences in temperature regulation was identified for male ferrets which was accompanied by prolonged viral replication in the upper respiratory tract after infection. Gene expression analysis of the nasal turbinates indicated that 1-year-old female ferrets had significant increases in interferon response genes post infection which were delayed in males. These results provide insight into COVID-19 and suggests that older males may play a role in viral transmission due to decreased antiviral responses.